Climate predicts which sex acts as helpers among cooperatively breeding bird species. (January 2017) - Zhang, Guoyue; Zhao, Qingtian; Møller, Anders Pape; Komdeur, Jan; Lu, Xin
Abstract : Among avian cooperative breeders, help in raising offspring is usually provided by males or by both sexes. Sex bias in helping should evolve in response to sex-specific ecological constraints on independent reproduction, with mate shortage for males and breeding vacancy shortage for each sex. Given that male-biased adult sex ratios are prevalent among birds, we predict that male-only helping mainly occurs in temperate species where fast population turnovers deriving from low adult annual survival allow all adult females to hold breeding vacancies, whereas some males overflow as helpers, and both-sex helping in tropical species where saturated habitats prevent not only males, but also females from breeding themselves. As expected, we found that across species, adult survival increased towards tropical zones and warmer climates, and higher adult survival tended to be associated with both-sex helping. Furthermore, sex bias in helping was predicted by latitude and ambient temperature. Our findings of demographic response of species to climate as a potential determinant of bias in helper sex uncover how ecological constraints operate to limit independent reproduction in sex-specific ways.